2008
DOI: 10.4269/ajtmh.2008.79.452
|View full text |Cite
|
Sign up to set email alerts
|

Five-year Experience with Type 1 and Type 2 Reactions in Hansen Disease at a US Travel Clinic

Abstract: Very few data have been reported on the epidemiology and clinical features of leprosy reactions in non-endemic settings. We performed a retrospective descriptive analysis to define the frequency and features of Type 1 and Type 2 leprosy reactions in a cohort of patients followed at a US travel and tropical medicine clinic in a 5-year period. We identified that leprosy reactions presented in 10/14 (71.4%) patients with leprosy seen at our clinic. We identified that leprosy reactions occur frequently among patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
11
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 9 publications
6
11
1
Order By: Relevance
“…leprosy frequency of reaction was higher. Similar result was found in other studies [9][10][11][12][13]. So these groups of patients are in need of strong surveillance for development of reaction.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…leprosy frequency of reaction was higher. Similar result was found in other studies [9][10][11][12][13]. So these groups of patients are in need of strong surveillance for development of reaction.…”
Section: Discussionsupporting
confidence: 80%
“…Frequency of reaction was observed to be higher in other studies than that observed in present one [7][8][9][10][11] which may be due to variability in follow up period. Our study found that, around 2/3 of patients having reaction was identified at diagnosis of leprosy; rest 1/3 developed features of reaction during or even after successful treatment of leprosy.…”
Section: Discussioncontrasting
confidence: 57%
“…Individuals who exhibit reactive outbreaks of leprosy are more susceptible to neural damage and possible sequelae [6,20,23]. In this study, although only 13.3% of the samples had a leprosy reaction, this variable was significant for the development of disability.…”
Section: Discussionmentioning
confidence: 69%
“…The impairment of nerve trunks has the potential to cause physical disabilities due to the immune system's action against the bacillus [6]. Its extent depends on the clinical form of the disease and the exacerbation phenomena during leprosy reaction episodes [7,8] Information on the number of people with disabilities/deformities due to leprosy remains limited.…”
Section: Introductionmentioning
confidence: 99%
“…One of the main reasons for requiring medical care is to manage permanent neurological disability and its consequences, such as skin and soft tissue infections, chronic nonhealing ulcers associated with neuropathic (Charcot) joints secondary to peripheral nerve dysfunction, and chronic leprosy reactions, which can take place months or even years after the completion of MDT (82). If diagnosis is delayed because of problems of access to health care and unfamiliarity with HD among physicians in the host country, long-term problems associated with nerve damage are more likely.…”
Section: International Migrationmentioning
confidence: 99%